Analisis Isi Pemberitaan Politik tvOne, MetroTV, dan RCTI menjelang Pemilihan Presiden 2019 di Indonesia - Muchlis Muchlis (Jurnal Ilmu Komunikasi, 2021)
This study aims to describe the tendency of the content of political news messages by television media tvOne, MetroTV, and RCTI ahead of the 2019 presidential election in Indonesia. This study uses a content analysis approach. The results of this study indicate that the tendency of the message content of political news broadcast by television media; (1) tvOne through the news how are you in Indonesia in the morning, the news at noon, and the news in the evening; (2) Metro TV through Indonesian good morning news, afternoon metro; (3) RCTI, through news programs about morning news, afternoon news, and evening news, during March 2019. From the three television media, it was found that news programs were dominated by political reports that discussed presidential candidate pairs. and vice-presidential candidate number 01 (Joko Widodo-Ma'ruf Amin) compared to presidential and vice-presidential candidates serial number 02 (Prabowo Subianto-Sandiaga Uno).